Neuroimmunomodulatory properties of laquinimod - P.G. Amrutha; Sonyanaik Banoth; Janardhan Banothu (Brain Disorders, 2024)
Laquinimod (ABR-215062) is a quinolone-3-carboxamide derivative, which is an orally active immunostimulatory drug molecule and is being developed for multiple sclerosis cases like relapsing-remitting multiple sclerosis (RRMS) and chronic progressive multiple sclerosis (CPMS). Laquinimod may mediate its effects by regulating pro-inflammatory immune responses and interfering with cell trafficking, in addition to possibly acting directly in the central nervous system to prevent demyelination and axonal injury. Nowadays, its benefits are extended further to various other neurodegenerative illnesses. Recently, it was found that laquinimod can exert only minimal effects in the clinical trials for both PPMS and RRMS making it not suitable for the treatment. However, cannot be completely neglected its pharmacological effect for curing disease progression in MS. Modification of the core structure can contribute to a better candidate for the treatment of MS. We have systematically reviewed the literature reported and highlighted the effect of laquinimod therapy not only on multiple sclerosis (MS) patients but also on a variety of other neurodegenerative disorders. Hence, this review can aid the research community in the design and development of novel chemical entities for the effective treatment of neurodegenerative disorders (NDDs).